Information Technology and Business Communication: Exploring the Use and Challenges of ICT in Business Management (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Data and Communication Technology (ICT) is an essential piece of business the heads now-a-day. It is inevitable for the smooth running of business free of size and multifaceted design wherever on the world. As a result of the quick improvement of ICT and its colossal use in all circles of our lives, organizations are similarly affected by it. By and by, organizations are managing their resources by using ICT support that is helping them with playing out their tasks faster and careful than already. Regardless, the non-modern countries like nonstandard are at this point endeavoring to introduce ICT maintains in each part of organizations. In any case, in view of an outstandingly strong culture at work place, this effort is defeated liberally. Accordingly, this paper targets perceiving the current status of the use of ICT in business the board and its troubles it faces. Helper data have been essentially used for coordinating this assessment which was accumulated from the different business reports and the journal papers. An experience survey was in like manner drove among the senior managers of the business houses were also associated with the assessment. Results show that the usage of ICT is low in the little and medium business attempts while the colossal organizations houses are using ICT maintains. Results in like manner show that the usage of ICT basically depends upon the multifaceted nature and the possibility of the business. The finance managers who have ICT capability, they are for the most part using ICT maintains in the organization of their organizations. This assessment suggests that the business houses in India ought to use ICT backing to fabricate the efficiency at their work. Nevertheless, this is consistently depends upon the ICT establishment of the nation by and large.